PERAN FINANCIAL PERFORMANCE SEBAGAI PEMEDIASI UNTUK PENGARUH ANTARA INDEPENDENT COMMISSIONERS DAN MANAGERIAL OWNERSHIP TERHADAP CORPORATE VALUE PADA BANKING CORPORATE YANG GO PUBLIC - Yohanes Mardinata Rusli; Piter Nainggolan (Jurnal Penelitian Akuntansi (JPA), 2021)
This study aims to examine and analyze: (i) the effect of independent commissioners and managerial ownership on corporate value; (ii) the role of financial performance as a proxy for the Return on Assets variable to influence independent commissioners and managerial ownership on corporate value. This study uses secondary data, the sample in this study is banking sector companies listed on the Indonesia Stock Exchange for the period 2016 – 2019. The number of companies that are sampled are 14 banking sector companies with an observation period of 4 (four) years and using the purposive sampling method. . The method of analysis in this study is multiple linear regression analysis using the SPSS program. Hypothesis testing uses a significance level of 5%. The results of the classical assumption test are that the data is normally distributed, and there is no multicollinearity, no Heteroscedasticity, and no autocorrelation. The results of this study state that: (i) independent commissioners have a significant and positive effect on corporate value; (ii) institutional ownership has a significant and negative effect on corporate value; (iii) financial performance can mediate the influence between independent commissioners on corporate value; (iv) financial performance does not mediate the influence of managerialownership and corporate value